The crystal structure of 3-benzyl-1-((8-(benzyloxy)quinolin-2-yl)methyl)-1H-imidazol-3-ium hexafluorophosphate, C27H24N3OF6P - Jiewei Luo; Shilu Zhang; Yiming Liu; Bo Zhao (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C27H24N3OF6P, monoclinic, Cc (no. 9), a = 18.0589(18) Å, b = 12.5100(9) Å, c = 13.3659(12) Å, β = 124.522(7)°, V = 2487.9(4) Å3, Z = 4, Rgt(F) = 0.0437, wRref(F2) = 0.1141, T = 113(2) K.